Carboxymethyl chitosan stabilized AuNPs/ACP nanohybrids in enamel white spot lesions - Chen, Xiaohua; Liu, Hengyu; Zhang, Qianqian; Chen, Xuehua; Wang, Lihui; Yu, Yanling; Hao, Yuanping (Frontiers in Bioengineering and Biotechnology, 2024)
Acidic bacterial biofilms-associated enamel white spot lesions (WSLs) are one of the hallmarks of early caries, causing demineralization and decomposition of dental hard tissues. Therefore, to effectively prevent and treat WSLs, it is important to inhibit the activity of cariogenic bacteria while promoting the remineralization of demineralized enamel.Amorphous calcium phosphate (ACP) favors hard tissue remineralization due to its biological activity and ability to release large amounts ofCa 2+ and PO 4 3-.However, ACP-based biomineralization technology is not effective due to its lack of antimicrobial properties. Here, carboxymethyl chitosan (CMCS) was employed as a reducing agent and stabilizer, and dual-functional nanohybrids CMCS/AuNPs/ACP with biofilm resistance and mineralization properties were successfully synthesized.The addition of AuNPs enhances the antimicrobial activity and participates in regulating the formation of hydroxyapatite (HAp). The nanohybrids exhibited significant destructive effects against cariogenic bacteria and their biofilms and showed bactericidal activity under bacteria-inducedacidic